What is an appropriate age to stop screening for colorectal cancer?. Issue 5 (May 2016) - Jawaid, Muhammad Mustafa
Abstract : Evidence‐Based Answer : Screening patients 75 to 85 years of age with colonoscopy has a small benefit in life‐years gained but at significant cost, leading the US Preventive Services Task Force (USPSTF) to recommend stopping routine screening at age 75 (SOR: B, decision analysis). However, the increasing proportion of colorectal cancers (CRC) diagnosed in patients older than 75 in recent years may shift the balance (SOR: C, case‐series).